DUKUNGAN SOSIAL YANG MENDORONG PERILAKU PENCEGAHAN SEKS PRANIKAH PADA REMAJA SMA X DI KOTA SURABAYA - Chitra Diana Rahmawati; Shrimarti Rukmini Devy (Universitas Airlangga, 2016)
The number of premarital sex among adolescents have been increasing. Based on BKKBN’sreport (2014), 46% of adolescents aged 15–19 years old already had premarital sex experience. Therefore, it requires preventions to solve adolescents’ premarital sex problems. This study aims to identify social support to preventive eff orts against premarital sex of high school students X in Surabaya.This descriptive study used qualitative research design and purposive sampling technique to determine the number of sample. Indepth interviewed conducted on 32 informants that were consist of 10 students, 10 close friends, 10 parents and 2 teachers. The results showed that social support especially fromfamilies who provide religious education, contribute to shaping the character of the teens themselves than support from friends and school. The preventive eff orts against premarital sex that can be done are: not dating, be selective in friendship, strengthen their faith and prayers, limiting the friendship, being ina relationship only for good reasons, not watching porn, avoid opposite-sex friends with bad manners, not coming home late at night, being resolute over their principles, learn the danger of premarital sex behavior, widen their social network, and being more active in social activities and hobbies.Keywords: preventive action, premarital sex, adolescents